Enhanced under frequency load shedding (UFLS) schemes performance in Sabah Grid System - Selamat, Mohd Khairul Zawawi (2013)
In the last five decade, peoples can survive successfully even without the existing of electrical energy. Nowadays, electricity is one of the important aspects for human being to run their daily life. Generation capacity should increase in proportion to the increase of its loads, but, if there are sudden changes in the system generation capacity through loss of generator or due to line tripping can produce severe generation-load imbalance. Under frequency load shedding scheme is implemented to restore power system frequency stability if system frequency drops below the operational set point during major disturbance such as lost of generation. Different countries/utility companies have their own philosophies in implementing the under frequency load shedding scheme. Generally, it is based on country/utility requirements, e.g. the overall power system network and the country’s demographic. As the main power utility in Sabah, Sabah Electricity Sdn Bhd (SESB) takes the responsibility to ensure that the daily operation are always operated in a reliable and secure condition in supplying power to the consumers. This project presents the principles and implementation of the under frequency load shedding (UFLS) scheme and conducted through simulation of 150,000 test bus-system in Sabah Grid System. The performance of the existing schemes under various conditions of disturbance were compared and analyzed. All the simulation works were performed using Siemens PTI software Power System Simulator for Engineering (PSS/E).